Early Gender Gaps among University Graduates - Marco Francesconi; Matthias Parey (Institute of Labor Economics (IZA), 2018)
We use data from six cohorts of university graduates in Germany to assess the extent of gender gaps in college and labor market performance twelve to eighteen months after graduation. Men and women enter college in roughly equal numbers, but more women than men complete their degrees. Women enter college with slightly better high school grades, but women leave university with slightly lower marks. Immediately following university completion, male and female full-timers work very similar number of hours per week, but men earn more than women across the pay distribution, with an unadjusted gender gap in full-time monthly earnings of about 20 log points on average. Including a large set of controls reduces the gap to 5-10 log points. The single most important proximate factor that explains the gap is field of study at university.
Keywords: J16; J31; J71; 330; gender wage gap; field of study; university graduates; Germany